The Efficacy of a Silicone Sheet in Postoperative Scar Management. (September 2016) - Kim, Jin Sam; Hong, Joon Pio; Choi, Jong Woo; Seo, Dong Kyo; Lee, Eun Sook; Lee, Ho Seong
ABSTRACT: OBJECTIVE: Silicone gel sheeting has been introduced to prevent scarring, but objective evidence for its usefulness in scar healing is limited. Therefore, the authors' objective was to examine the effectiveness of silicone gel sheeting by randomly applying it to only unilateral scars from a bilateral hallux valgus surgery with symmetrical closure. DESIGN: In a prospective randomized, blinded, intraindividual comparison study, the silicone gel sheeting was applied to 1 foot of a hallux valgus incision scar (an experiment group) for 12 weeks upon removal of the stitches, whereas the symmetrical scar from the other foot was left untreated (a control group). The scars were evaluated at 4 and 12 weeks after the silicon sheet application. The Vancouver Scar Scale was used to measure the vascularity, pigmentation, pliability, height, and length of the scars. Adverse effects were also evaluated, and they included pain, itchiness, rash, erythema, and skin softening. RESULTS: At weeks 4 and 12, the experiment group scored significantly better on the Vancouver Scar Scale in all items, except length ( P < .05 for all except the length of scar), compared with the control group. In all items, adverse effects of the experiment group were significantly lower than those of the control group at week 12, suggesting that direct attachment of the silicone sheet does not cause adverse effects ( P < .05). CONCLUSIONS: To the authors' knowledge, this is one of the first models to minimize bias related to scar evaluation by using symmetrical scars. The early silicone sheet application did show a significant improvement in prevention of postoperative scarring.